Предмет: Алгебра,
автор: Erkeen7D
(x+y)(x+y)-(4x^2-y^2) - Упростите выражение, помогите пожалуйста
Ответы
Автор ответа:
0
Ну что ж, здесь мы используем ФСУ:
а^2-в^2 = (а-в)(а+в)
(х+у)(х-у)-(4х^2-у^2) = х^2-у^2-4х^2+у^2=
=-3х^2
а^2-в^2 = (а-в)(а+в)
(х+у)(х-у)-(4х^2-у^2) = х^2-у^2-4х^2+у^2=
=-3х^2
Автор ответа:
0
Спасибо, очень помог!
Автор ответа:
0
Не за что :) Обращайтесь
Похожие вопросы
Предмет: История,
автор: mikaelananna1
Предмет: Информатика,
автор: daniildemydov
Предмет: Литература,
автор: margaritapugacheva75
Предмет: Химия,
автор: Deutschland96
Предмет: Биология,
автор: Rauau1999